Influence of a 2-km swim on the cycling power-duration relationship in triathletes - Rothschild, J.; Sheard, A. C.; Crocker, G. H. (The Journal of Strength and Conditioning Research, 2022)
Triathletes must cycle after swimming, and so, it is important to understand how cycling performance may be affected by prior swimming. Therefore, the purpose of this study was to determine the effects of a 2-km swim at a self-selected race-pace intensity on the cycling power-duration relationship. Eighteen trained triathletes (12 M, 6 F; 37.1 ± 10.6 years, Vo2max 54.8 ± 10.1 ml·kg-1·min-1) performed two 3-minute all-out cycling tests (3MTs) on separate days with one 3 MT immediately after a 2-km swim (swim-bike [SB]) and one without prior swimming (bike-only [BO]). The power-duration relationship was expressed as the total work done (TWD) and subdivided into end-test power (EP) and work done above EP. To assess swimming intensity, heart rate (HR) was continuously monitored during the 2-km swim and blood lactate was assessed on completion of the swim. End-swim lactate was 4.2 ± 1.8 mM, and mean swimming HR was 147 ± 18 b·min-1. The 2-km swim decreased TWD during the 3MT by 6% (BO: 62.8 ± 12.7 kJ; SB: 58.9 ± 13.4 kJ; p = 0.001) though neither EP (BO: 281 ± 65 W; SB: 269 ± 68 W; p = 0.102) nor work done above EP (BO: 12.1 ± 3.8 kJ; SB: 10.5 ± 4.2 kJ; p = 0.096) differed between trials. In conclusion, TWD while cycling decreases after a 2-km race-pace swim. Results from this study suggest that triathletes should determine racing cycling power following a simulated race-pace swim.